Pengaruh Kualitas Pelayanan, Kualitas Produk, Lokasi Dan Persepsi Harga Terhadap Kepuasan Konsumen - Sifahudztahanina Sifahudztahanina; Moeljono Moeljono; Aep Saeafullah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The aim of this research is to examine the analysis of the influence of service quality, product quality, location and price perception on consumer satisfaction at the Mang Khalim grated coconut stall located in the Ngampel Kendal traditional market. Previous research obtained different consumer satisfaction results. Therefore, this research aims to review previous researchers regarding consumer satisfaction. This research had 98 respondents from consumers of Mang Khalim grated coconut stalls using the Snowball Sampling technique. The analysis method in this research uses the SmartPLS 3.0 tool. The results of this research show that service quality and price perception have a negative and insignificant influence on consumer satisfaction. Meanwhile, product quality and location have a very positive influence but do not have a significant influence on consumer satisfaction.